2011
DOI: 10.1115/1.4003714
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Inflow Conditions on the Heavy-Duty Gas Turbine Exhaust Diffuser Performance

Abstract: The flow in exhaust diffusers along with the channel geometry strongly depends on the inflow conditions, including Mach number level, total pressure distribution, flow angle, and turbulence. In the first part of this paper, the impact of these parameters is analyzed using computational fluid dynamics, experimental data from the test rig, and field measurements. A widespread opinion is that the optimal condition for the diffuser is an axial uniform inflow. However, it is shown in this paper that nonuniform pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Vassiliev et al ascertained that diffuser performance is influenced by inlet Mach number, total pressure distribution, flow angle, and turbulence characteristics of the inflow [10].…”
Section: Diffuser Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Vassiliev et al ascertained that diffuser performance is influenced by inlet Mach number, total pressure distribution, flow angle, and turbulence characteristics of the inflow [10].…”
Section: Diffuser Researchmentioning
confidence: 99%
“…or, using the pressure coefficient , rr , , rr ≈ . Σ + r ,i al (10) with r being the diffuser effectiveness at reference operating point. The underlying Σ model was subsequently tested and expanded to correlations for various diffuser opening angles in [13].…”
Section: Stabilisation Numbermentioning
confidence: 99%
“…However, these charts rely on simplified inflow conditions and require additional, semi-empirical corrections to account for non-uniform inflow conditions. For example, Vassiliev et al (2011) showed that the diffuser performance depends on the inlet Mach number, total pressure distribution, flow angle, and turbulence characteristics.…”
Section: Stabilisation Numbermentioning
confidence: 99%
“…15 The obtained results show that the vortices of the wakes at the rotor tip lead to the higher static pressure recovery performance in the annular diffuser compared with the flow condition without consideration of the upstream vortices. Vassiliev et al 16 conducted the effects of the inlet Mach number, total pressure distribution, flow angle, and turbulence on the flow field of the exhaust diffuser using numerical simulation and experimental method. They demonstrated that non-uniform pressure distribution and moderate swirl can improve the performance of the exhaust diffuser.…”
Section: Introductionmentioning
confidence: 99%